Pengaruh Komunikasi Bisnis Strategis terhadap Optimalisasi Human Capital dalam Menghadapi Era Disrupsi Digital: Pengaruh Komunikasi Bisnis Strategis terhadap Optimalisasi Human Capital dalam Menghadapi Era Disrupsi Digital - Sasanti Sihsubekti; Muawanah Muawanah (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2026)
In the era of digital disruption, human capital optimization is key to an organization's sustainability and competitive advantage. However, a major challenge often faced is the failure to synergize internal communication patterns with dynamic business strategies. This study aims to analyze and measure the influence of strategic business communication on human capital optimization. Using a quantitative approach, data were collected through questionnaires from 100 employees of PT. Gema Nusantara Malang and analyzed using simple linear regression with the help of SPSS software. The results showed that strategic business communication had a positive and significant effect on human capital optimization with a coefficient of determination (R2) of 61.2%. This finding confirms that information transparency and clarity of organizational messages serve as important catalysts in improving employee competence and adaptability amidst massive technological change.